Enabling the sustainability transition in buyer–seller interactions: Strategic insights from sellers and buyers - Pia Hautamäki; Karina Burgdorff Jensen; Andrea Urbinati (Cleaner Production Letters)
Legislation is now compelling European firms to conduct their businesses in an environmentally sustainable manner. Also, customers are increasingly demanding sustainability aspects in business proposals, products and solutions. Thus, numerous firms are seeking effective sales-related strategies to enable a shift toward sustainable business practices and support their customers' sustainability transition. There is a paucity of studies within the context of buyer–seller interactions and lack of empirical understanding concerning sustainability transition and professional selling. Our study takes stock of this research gap by investigating how sales executives and their buyers in three countries enable the sustainability transition in buyer‒seller interactions. Leveraging the theoretical lens of relationship selling and drawing on qualitative research based on one-to-one interviews and focus-group interviews conducted in Finland, Denmark, and Italy, our study developed a model of sales strategies enabling sustainability transition in buyer‒seller interactions, both from the sellers' and buyers’ perspectives. These strategies can be categorized as context-driven, customer-driven, sales-driven, or joint-driven, depending on whether they are shaped by customers or sellers, or by collaborative efforts. Our study demonstrates that sales strategies influencing the sustainability transition in buyer–seller interactions vary based on the maturity level of sustainability within the firm, while firm size also matters. Our study contributes to the literature on sustainability transition in buyer‒seller interactions from a sales strategy perspective by delineating how sales firms can incorporate sustainability principles for their customers. This study also offers managerial suggestions for firms on how to implement sales strategies during sustainability transitions.